Access to healthcare for disabled individuals: An analysis of judgments of the European Court of Human Rights from an ethical perspective - Skuban-Eiseler, Tobias; Orzechowski, Marcin; Steger, Florian (Frontiers in Public Health, 2023)
Individuals with disabilities (ID) suffer from restricted access to healthcare. This contributes to their poorer health status and constitutes an ethical challenge. The aim of this research was to systematically analyze judgments of the European Court of Human Rights (ECtHR) to illustrate examples of restricted access to healthcare for ID. Through search in the ECtHR’s database we identified judgments dealing with access to healthcare for ID. The search resulted in n=329 judgments, of which n=55 were included in the analysis. A descriptive statistic was performed on Articles of the European Convention on Human Rights and violation of these articles. Qualitative thematic analysis was conducted to group the judgments in thematic categories. Most applications were filed against Russia (n=23), followed by Poland (n=8) and Ukraine (n=7). The youngest applicant was 18, the oldest 72 years old. An overwhelming majority of cases dealt with disabled prisoners. Most of the judgments involved Article 14 and Article 8. We identified seven partially overlapping categories representing thematic patterns in the analyzed judgments. Any restriction of access to healthcare can be considered a violation of human rights. However, the results show a relatively low total number of judgments dealing with limited access to healthcare for ID. This could be a further confirmation of the fact that ID still experience too little attention in our societies. Especially in the context of detention, ID are restricted from receiving the healthcare they require. Indirect ways of a restricted access to healthcare should not be overseen.